Teacher perceptions of communication impairment at screening stage in preschool children living in Patras, Greece - Okalidou, Areti; Kambanaros, Maria (My University, 2001)
The general aim was to obtain piloting data for a series of experiments about the prevalence of communication impairment in preschool children in Greece. At this screening stage of the overall project, teacher perceptions of communication impairment in 57 kindergartens servicing 1113 children were examined via a questionnaire distributed in the urban region of Patras. The specific research goals were (1) to screen for specific categories of communication impairment such as articulation/phonology, receptive language, expressive language and pragmatics, hearing, stuttering, and voice, as they appear in the mainstreamed kindergarten population and (2) to offer comparative information on sex differences in communication impairment(s). The information was gathered by administration of a Greek-adapted version of the Communication Checklist for Pre-school Teachers, which was administered three times to obtain validity and reliability measures. The results were analysed separately for two studies (original and follow-up) and indicated teacher estimates of 14.4Þ18.7% for communication impairment in kindergarten children of the Patras region. Prevalence was higher for boys than for girls. Analysis of specific communication areas revealed that prevalence varies according to gender and category of communicative impairment. The limitations and follow-up needs of this study are discussed.
Keywords: Prevalence; Communication disorde rs; Speech & language disorders; Greek children